2017
DOI: 10.3389/fpls.2017.02124
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Crop Rhizosphere: Impact of Domestication on Root Exudates in Tetraploid Wheat (Triticum turgidum L.)

Abstract: Domestication has induced major genetic changes in crop plants to satisfy human needs and as a consequence of adaptation to agroecosystems. This adaptation might have affected root exudate composition, which can influence the interactions in the rhizosphere. Here, using two different soil types (sand, soil), we provide an original example of the impact of domestication and crop evolution on root exudate composition through metabolite profiling of root exudates for a panel of 10 wheat genotypes that correspond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
88
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 39 publications
2
88
0
Order By: Relevance
“…The metabolites detected in B. distachyon root exudates in this study (Table S3) were comparable to metabolites detected in exudates of other grasses such as wheat (Iannucci et al , 2017), maize (Carvalhais et al , 2011), rice (Bacilio-Jiménez et al , 2003), Avena barbata (Zhalnina et al , 2018) and dicots such as Arabidopsis (Chaparro et al , 2013). Similarly, the B. distachyon exudation profile varied with developmental stage, as reported for other plants (Fig.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The metabolites detected in B. distachyon root exudates in this study (Table S3) were comparable to metabolites detected in exudates of other grasses such as wheat (Iannucci et al , 2017), maize (Carvalhais et al , 2011), rice (Bacilio-Jiménez et al , 2003), Avena barbata (Zhalnina et al , 2018) and dicots such as Arabidopsis (Chaparro et al , 2013). Similarly, the B. distachyon exudation profile varied with developmental stage, as reported for other plants (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…S2). Interestingly, altered root:shoot ratios were recently also detected for wheat genotypes grown in different soils (Iannucci et al , 2017), suggesting that different soils might affect root:shoot ratio and possibly also metabolic profiles in different ways.…”
Section: Discussionmentioning
confidence: 99%
“…This prevents stem lodging that arose in response to the increase in size and biomass of the spike, because of the massive fertilization of fields implemented after the Second World War (Berry et al, 2015;Borojevic & Borojevic, 2005). Modern genotypes may differ from ancient genotypes in terms of metabolic composition (Di Loreto et al, 2018;Gotti et al, 2018;Iannucci, Fragasso, Beleggia, Nigro, & Papa, 2017;Shaposhnikov et al, 2016) and root architecture (Beyer et al, 2018;Horst, Abdou, & Wiesler, 1993;Pour-Aboughadareh, Ahmadi, Mehrabi, Moghaddam, & Etminan, 2017;Shaposhnikov et al, 2016;Siddique et al, 1990), which is likely to affect plant × PGPR interactions. Against this background, however, results also revealed that (a) many ancient genotypes were not effective for interaction (especially colonization) with P. kilonensis F113, whereas (b) interaction effectiveness with F113 had been maintained in a significant proportion of modern wheat genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…pesticides, fertilizer), influence the below-ground diversity and function of soil microbes (Vries & Wallenstein, 2017), however, it is less clear if crops themselves cultivate different below-ground interactions compared to their wild relatives. Crops have reduced genetic diversity, which could influence the type, strength or diversity of interactions experienced belowground (Pérez-Jaramillo et al, 2016), and differences in root architecture (Schmidt, Bowles, & Gaudin, 2016) and root exudates (Iannucci, Fragasso, Beleggia, Nigro, & Papa, 2017) among crops and wild relatives can be pronounced. Yet, it is totally unknown whether domestication-mediated differences in rhizosphere microbes have functional consequences in the context of plant-soil feedback.…”
Section: Introductionmentioning
confidence: 99%